Attitudes Toward Providing Open Access for Use of Biospecimens and Health Records: A Cross-Sectional Study from Jordan - Kamal M Al-Shami (15483548) (2023)
Purpose Biospecimen repositories and big data generated from clinical research are critically important in advancing patientcentered healthcare. However, ethical considerations arising from reusing clinical samples and health records for subsequent research pose a hurdle for big-data health research. This study aims to assess the public’s opinions in Jordan toward providing blanket consent for using biospecimens and health records in research. Participants and Methods A cross-sectional study utilizing a self-reported questionnaire was carried out in different cities in Jordan, targeting adult participants. Outcome variables included awareness of clinical research, participation in clinical research, and opinions toward providing open access to clinical samples and records for research purposes. Descriptive analysis was utilized for reporting the outcome as frequency (percentages) out of the total responses. Univariate and multivariate logistic regression were used to investigate the association between independent variables and the outcome of interest. Results A total of 1033 eligible participants completed the questionnaire. Although the majority (90%) were aware of clinical research, only 24% have ever participated in this type of research. About half (51%) agreed on providing blanket consent for the use of clinical samples, while a lower percentage (43%) agreed on providing open access to their health records. Privacy concerns and lack of trust in the researcher were cited as major barriers to providing blanket consent. Participation in clinical research and having health insurance were predictors for providing open access to clinical samples and records. Conclusion The lack of public trust in Jordan toward data privacy is evident from this study. Therefore, a governance framework is needed to raise and maintain the public’s trust in big-data research that warrants the future reuse of clinical samples and records. As such, the current study provides valuable insights that will inform the design of effective consent protocols required in data-intensive health research. Other Information Published in: Patient Preference and Adherence License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.2147/ppa.s402769